Knot theory - Manturov Vassily (Boca Raton Chapman & Hall, 2004)
These topics include the Khovanov generalization of the Jones polynomial, the Krammer-Bigelow faithful representation of the braid group, a systematic treatment of algorithms for braid recognition, the author's theory of atoms and d-diagrams, the theory
Keywords: Knot theory